078 A case of non-convulsive status epilepticus (NCSE) as first presentation of sporadic creutzfeldt-jakob Disease (sCJD). (23rd August 2021) - Gagen, Luke; Lefever, Kristen; Schweitzer, Daniel; Clarke, Laura; O'Gorman, Cullen; Swayne, Andrew
Abstract : Objectives sCJD is a neurodegenerative prion disease characterised by rapidly progressive neuropsychiatric symptoms and movement disorder. Seizures are an uncommon first presentation of sCJD. We present a case of a 71 year-old female in whom presented in NCSE. Methods: Single Case Report. Results: A 71-year-old female initially presented with higher cortical impairment characterised by visuospatial deficits and apraxia suggestive of parietal lobe dysfunction. Subsequent MRI showed multifocal patches of gyriform diffusion restriction – cortical ribboning – predominantly in the right parietal cortex. Autoimmune and metabolic cerebrospinal fluid (CSF) testing were unremarkable for markers of autoimmune or infectious encephalitis. EEG demonstrated NCSE arising from this right hemisphere lesion, with severe diffuse encephalopathy. A ward-based anti-epileptic drug regime was instituted without success. ICU management with midazolam infusion and intubation for NCSE was required. Clinically and electrographically the patient improved over a two-week period, with resolution of NCSE on repeat EEG. Unfortunately however a repeat MRI on Day 17 of admission demonstrated progression of cortical ribboning beyond the initial focus across hemispheres. This in combination with a positive 14-3-3 and tau protein on CSF, raised the likelihood of sCJD. Marked clinical deterioration followed extubation, with palliative care involvement and end of life planning. The diagnosis of sCJD was confirmed with brain biopsy at autopsy. Conclusion: The case is notable as it is rare for sCJD to present early with NCSE 1 and reinforces the need for atypical presentations to prompt exploration of a broader differential diagnosis in the context of unexpected investigation findings. Reference: Espinosa PS, Bensalem-Owen MK, Fee DB. Sporadic creutzfeldt–jakob disease presenting as nonconvulsive status epilepticus case report and review of the literature. Clinical Neurology and Neurosurgery 2010 July 1;112(6):537–40.